2005
DOI: 10.2223/jped.1404
|View full text |Cite
|
Sign up to set email alerts
|

Safe school

Abstract: Implementation of safe schools represents a promising new direction for school-based preventive work. It is important to note that a safe school should intervene not only in its physical structure, but it should also make it as safe as possible by gathering the school community through health education, and mainly encouraging healthy behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
1
11
0
8
Order By: Relevance
“…The health professionals narrated the participation in health programs in the school, however the poisoning event, within the referential of the school health promoter, 27 must go beyond school walls. The participation of all those responsible, including health professionals in the education sector and the community, is essential, forming work fronts so that everyone is alerted and mobilized for the benefit of the children.…”
Section: Discussionmentioning
confidence: 99%
“…The health professionals narrated the participation in health programs in the school, however the poisoning event, within the referential of the school health promoter, 27 must go beyond school walls. The participation of all those responsible, including health professionals in the education sector and the community, is essential, forming work fronts so that everyone is alerted and mobilized for the benefit of the children.…”
Section: Discussionmentioning
confidence: 99%
“…22 When considering that there is a low demand from teenagers to health services 23 , the school appears, then, much important and crucial for this sector as a partner, assuming a growing importance on the health promotion and disease prevention; therefore, integrating educators, parents, students, health professionals and community members in an effort to transform schools into healthy environments. 24 Given this reality, this documentary research demonstrated a concern of several professional classes with the health of adolescent school, starting with the oral health through studies carried out by the field of dentistry and public health.…”
Section: Resultsmentioning
confidence: 99%
“…The pedagogical dimension was made up of 14 items and looked at themes and activities related to the learning process, from a perspective of attaining healthy environments. Items considered relevant and feasible to be analyzed individually or cross-sectionally were: healthy eating and physical activity 14 , personal hygiene care 26 , 27 , sexual and reproductive health 8 ; prevention of licit and illicit drug use 2 , 19 , 22 ; culture of peace and human rights and personal interaction skills in terms of inclusion, respect, initiative and tolerance 16 , 19 , 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The relational dimension, with 13 items, linked the conditions that were considered necessary to construct an ethos to promote a pleasant environment from a social point of view, which focused on the relationships and the conditions that had been established within the school community. Aspects regarding the relationship between students, teachers and the community, the presence of violence, actions to promote protagonism and respect for rules of coexistence were also considered 3 , 19 , 27 , 29 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation